Determination of total phthalates in edible oils by high‐performance liquid chromatography coupled with photodiode array detection. Issue 5 (28th January 2016) - Xie, Qilong; Sun, Dekui; Han, Yangying; Jia, Litao; Hou, Bo; Liu, Shuhui; Li, Debao
Abstract : The previously reported procedure for the determination of the total phthalate in fatty food involved the extraction of phthalates using chloroform/methanol followed by the removal of the solvents before alkaline hydrolysis requiring 20 h and derivatization of phthalic acid. In this study, a phase‐transfer catalyst (tetrabutylammonium chloride) was used in the liquid–liquid heterogeneous hydrolysis of phthalates in oil matrix shortening the reaction time to within 25 min. The resulting phthalic acid in the hydrolysate was extracted by a novel molecular complex based dispersive liquid–liquid microextraction method coupled with back‐extraction before high‐performance liquid chromatography coupled with photodiode array detection. Under the optimal experimental conditions, the linearity of the method was in the range of 0.5–12 nmol/g with the correlation coefficients ( r ) >0.997. The detection limit (S/N = 3) was 0.11 nmol/g. Intraday and interday repeatability values expressed as relative standard deviation were 3.9 and 7.1%, respectively. The recovery rates ranged from 82.4 to 99.0%. The developed method was successfully applied for the analysis of total phthalate in seven edible oils.